2008
DOI: 10.1159/000149580
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label Pilot Study of Acetylcholinesterase Inhibitors to Promote Functional Recovery in Elderly Cognitively Impaired Stroke Patients

Abstract: Background: Impairments in cognition and motivationare common after stroke and predict poor functional recovery. Pharmacological agents that enhance cognition and/or diminish apathy may, when combined with traditional rehabilitative efforts, improve functional recovery. We investigated the feasibility of using acetylcholinesterase inhibitors in older patients with acute post-stroke cognitive impairment and examined their effects on functional recovery. Methods: This 12-week open-label study prospectively treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 36 publications
(22 reference statements)
0
41
0
Order By: Relevance
“…Two articles reported on apathy prevalence in the same cohort at different time points. 23,44 Results reported in these articles were combined using size weighted averages for all analyses except for those regarding time since stroke and population age.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two articles reported on apathy prevalence in the same cohort at different time points. 23,44 Results reported in these articles were combined using size weighted averages for all analyses except for those regarding time since stroke and population age.…”
Section: Resultsmentioning
confidence: 99%
“…43 In another small (n=22) open study, the acetylcholinesterase inhibitor donepezil had a modest beneficial effect on functional status, which was also associated with a reduction in apathy score. 44 In 5 case reports, a favorable effect of treatment with bromocriptine was reported, 14,[45][46][47][48] and in 3 with methylphenidate.…”
Section: Poststroke Apathy 853mentioning
confidence: 99%
See 1 more Smart Citation
“…), selective serotonin noradrenaline reuptake inhibitors (SNRI) [25] (reboxetine 3 mg b.i.d. ), acetylcholinesterase inhibitors [6,7] (donepezil 5 mg q.d. ), modafinil [26,27] (100 mg/day), methylphenidate [9] (20 mg/day), and memantine [28] (20 mg/day).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, some clinical studies showed a beneficial effect with different agents [3,4,5,6,7,8,9] while others did not [10,11,12,13,14,15]. Thus, the clinical evidence of benefit of this treatment approach is weak, as most of the aforementioned studies are limited by small sample sizes and narrow inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%